Mites resistance of rubber tree clones in the northwestern Sao Paulo State conditions - Vieira, Marineide Rosa [UNESP]; Celoto, Fernando Juari [UNESP]; Scaloppi Junior, Erivaldo Jose; Agustini, Jose Antonio [UNESP] (Inst Agronomico, 2017)
Calacarus heveae Feres (Eriophyidae) and Tenuipalpus heveae Baker (Tenuipalpidae) can cause heavy defoliation on rubber trees. From the view of Integrated Pest Management, the use of clones with resistance is an important control strategy. The objective of this study was to evaluate the resistance of rubber tree clones to infestation of these mites. The experiment was carried out in Votuporanga, Sao Paulo State, with IAC 301, IAC 330, IAN 4493, OS 22, PB 233, PB 254, PC 96, PC 119, PC 140, PC 141, PM 10, and RRIM 600 clones, totaling 12 treatments and 3 replicates, in randomized blocks experimental design. The population assessment of C. heveae and T. heveae was performed in laboratory by counting mites and exuviae presence in 6 leaflets per plot. The defoliation levels were evaluated with a score scale varying from 0 (no defoliation) to 5 (total defoliation). IAC 301, PB 254, and PC 119 clones have resistance by no preference and/or antibiosis to C. heveae mite.
Keywords: Hevea brasiliensis; Calacarus heveae; Tenuipalpus heveae; Acari; host plant resistance